2021
DOI: 10.1200/op.21.00343
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prevention: Time for Change

Abstract: Agency breast cancer prevention guidelines for other than hereditary cancers have not materially changed in 20 years; endocrine-targeted agents (then, tamoxifen; now, adding raloxifene and aromatase inhibitors) reduce good prognosis estrogen receptor (ER)–positive, progesterone receptor (PR)–positive cancers without reducing deaths from breast cancer. Across three tamoxifen placebo-controlled prevention trials (N = 23,360) begun almost 30 years ago, although there were 226 fewer breast cancer cases, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
(86 reference statements)
0
26
0
3
Order By: Relevance
“…98,118 Congruent with this concept, the greatest reduction is in tumors with these therapies that are ERα + . 126…”
Section: The Role Of Selective Er Modulators and Aromatase Inhibitors...mentioning
confidence: 99%
“…98,118 Congruent with this concept, the greatest reduction is in tumors with these therapies that are ERα + . 126…”
Section: The Role Of Selective Er Modulators and Aromatase Inhibitors...mentioning
confidence: 99%
“…• Postmenopausal women randomized to estrogen alone in the WHI's prospective, randomized, double-blind study were reported to have a persistent 23% reduced risk of breast cancer after 20 years of follow-up 16 and a 40% reduced risk of breast cancer mortality. 17 Among women with no prior HRT exposure (constituting the majority of perimenopausal women taking HRT as part of the study), the WHI reported no increased risk of breast cancer associated even with combination HRT (conjugated equine estrogen [CEE] + medroxyprogesterone acetate [MPA]) administration. 18 • A full-term pregnancy, which floods the body with both estrogen and progestogen, before age 20 years reduces the risk of subsequent breast cancer by 70%.…”
mentioning
confidence: 99%
“…In the companion to this article, Chlebowski et al 3 present a review of breast cancer prevention and eloquently summarize the decades of work that his group has spent researching this topic through the Women's Health Initiative (WHI). 4 To date, the only medications well-studied for breast cancer prevention are endocrine therapy, which includes selective estrogen receptor modulators and aromatase inhibitors, and there is no known survival benefit from this approach.…”
mentioning
confidence: 99%